Urban dystopia and epistemologies of hope. (August 2015) - Pow, C.P.
This paper takes issue with the dystopian views that have come to dominate research on privatized urban forms such as gated communities. Urban scholarship on gating is often overwhelmed by recurring case studies documenting the proliferation of urban fortressing and segregation that often warn of an impending urban dystopia with cities being besieged by neoliberal forces of privatism. Moving beyond such noir urban scholarship and universal pessimism, the paper argues for a more 'hopeful' research agenda by countering the overcoded mono-logic of urban fortification and segregation with a more nuanced perspective that underscores the differentiating dynamics and contingent nature of urban spaces.